Principle Analysis of Soil Electrical Conductivity Test Based on Pulsed Eddy Current. Issue 4 (March 2019) - Zhu, Wenyue; Zhang, Lin; Peng, Yaping; Zhang, Qi; Gao, Mingchao; Fu, Yingchun
Abstract: Nowadays, soil salinization is one of the major environmental geological disasters in the world. The rapid survey of soil conductivity through pulsed eddy current detection helps reflect the salinization degree, which can save cost and improve efficiency. In this paper, the basic principle of pulsed eddy current for soil conductivity detection is expounded, the detection depth of pulsed eddy current is theoretically analyzed, and the principle of soil conductivity detection based on pulsed eddy current is studied as well as analyzed.